The house on Vesper Sands : a novel - O'Donnell, Paraic (Tin House, 2021)
"London, 1893: high up in a house on a dark, snowy night, a lone seamstress stands by a window. So begins the swirling, serpentine world of Paraic O'Donnell's Victorian-inspired mystery, the story of a city cloaked in shadow, but burning with questions: why does the seamstress jump from the window? Why is a cryptic message stitched into her skin? And how is she connected to a rash of missing girls, all of whom seem to have disappeared under similar circumstances? On the case is Inspector Cutter, a detective as sharp and committed to his work as he is wryly hilarious. Gideon Bliss, a Cambridge dropout in love with one of the missing girls, stumbles into a role as Cutter's sidekick. And clever young journalist Octavia Hillingdon sees the case as a chance to tell a story that matters-despite her employer's preference that she stick to a women's society column. As Inspector Cutter peels back the mystery layer by layer, he leads them all, at last, to the secrets that lie hidden at the house on Vesper Sands"--